Utilization of the posterior iliac line for visualizing posterior column screws in obturator oblique view - Hongtao Li; Li Xu; Longxin An; Xiaojing Li; Linjing Zhang; Jun Liu; Kaili Zhai; Xuecheng Sun; Naibo Feng (PLoS ONE, 2026)
Purpose To evaluate whether posterior column screws penetrate the posterior cortical surface of the acetabulum when assessed using obturator oblique radiographic imaging. Methods Computed tomography (CT) scans were performed on the right acetabulum of 50 healthy adults to measure the angle (α) between the posterior wall of the acetabulum and the sagittal plane at the level of the femoral head’s maximal diameter. In addition, five cadaveric pelvises were subjected to C-arm fluoroscopic imaging. A 6 cm long, 1.5 mm Kirschner wire was positioned along the posterior surface of the acetabular posterior column, aligned with the greater sciatic notch, and imaged in both the 45° and α-degree obturator oblique views. The radiographic line visualized from the Kirschner wire in the obturator oblique view was defined as the posterior iliac line , and its anatomical relationship with the posterior surface of the posterior column was analyzed. Subsequently, a 2.5 mm Kirschner wire was inserted into the posterior column at the standard entry point for screw placement using an electric drill, with the wire tip intentionally positioned between the posterior iliac line and the posterior rim in the 45° obturator oblique view. The trajectory of the wire was assessed under both 45° and α-degree obturator oblique views to determine its relation to the osseous corridor. Results The measured angle between the posterior surface of the acetabular posterior column and the sagittal plane was (60.2 ± 2.5)°. In the 45° obturator oblique view, the posterior iliac line corresponded with the outer edge of the iliac crest superiorly and the outer edge of the ischium inferiorly, while the posterior wall was projected posterior to the midpoint of the posterior iliac line. In the α° obturator oblique view, the posterior iliac line maintained this alignment but intersected centrally with the posterior acetabular wall. The 2.5 mm Kirschner wire remained within the osseous corridor under the 45° view but potentially extended beyond it under the α° view. Conclusion When the posterior column screw is visualized posterior to the posterior iliac line in the 45° obturator oblique view, further assessment using a α° view is necessary. If the screw appears anterior to the posterior iliac line in the α° view, it indicates that the posterior cortical surface has not been breached.